2016
DOI: 10.1038/srep31614
|View full text |Cite
|
Sign up to set email alerts
|

Topology of chromosome centromeres in human sperm nuclei with high levels of DNA damage

Abstract: Several studies have shown that the ‘poor’ sperm DNA quality appears to be an important factor affecting male reproductive ability. In the case of sperm cells from males with the correct somatic karyotype but with deficient spermatogenesis, resulting in a high degree of sperm DNA fragmentation, we observed changes in the preferential topology of the chromosome 7, 9, 15, 18, X and Y centromeres. The changes occurred in radial localization and may have been directly linked to the sperm chromatin damage. This con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 56 publications
1
13
0
Order By: Relevance
“…Additionally, in most RCT males analysed in this study, repositioning of sex chromosomes was observed (X – 10/13; Y – 11/13), clearly suggesting their vulnerability to repositioning. This finding also strongly confirms previous data showing that the repositioning of sex chromosomes towards the sperm nuclear periphery accompanies disturbances in spermatogenesis in males with reproductive failure [2125, 27, 28, 55]. In control spermatozoa, preferential X chromosome localization was observed in the acrosomal area, which is the first region that interacts with the ooplasm during fertilization [6, 13, 2224, 52, 55, 56].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Additionally, in most RCT males analysed in this study, repositioning of sex chromosomes was observed (X – 10/13; Y – 11/13), clearly suggesting their vulnerability to repositioning. This finding also strongly confirms previous data showing that the repositioning of sex chromosomes towards the sperm nuclear periphery accompanies disturbances in spermatogenesis in males with reproductive failure [2125, 27, 28, 55]. In control spermatozoa, preferential X chromosome localization was observed in the acrosomal area, which is the first region that interacts with the ooplasm during fertilization [6, 13, 2224, 52, 55, 56].…”
Section: Discussionsupporting
confidence: 91%
“…The topology of chromosomes 4, 7, 8, 9, 10, 11, 18, X and Y was estimated in linear and radial measurement patterns, explained in Fig. 1, as developed by Zalenskaya and Zalensky [52] and successfully used in our previous topology studies [2225]. In the case of chromosomes involved in RCT, in addition to centromere-specific FISH probes, probes specific for subtelomeric regions were also used (colour combinations described previously [45, 47, 48]).…”
Section: Methodsmentioning
confidence: 99%
“…A study by Simon et al [62] , identified a positive correlation between the Comet and TUNEL assays ( r 2 = 0.126; P < 0.001) in couples undergoing ART. The TUNEL and SCSA assays exhibited similar results for SDF in infertile patients compared with a control population [63] and there was a strong correlation for the TUNEL and SCSA assays [64] .…”
Section: Correlation Amongst Different Sdf Assaysmentioning
confidence: 68%
“…This is supported by the fact that we did not record significant differences in the distribution of the chromosomes, in the four arbitrarily defined regions, when comparing WT and transgenic sperm ( Table 1 ). However, a recent study did show that high levels of DNA damage in human sperm (such as significant DNA fragmentation) could disrupt the position of the centromeres [ 68 ]. This suggested that chromosome 3D organization may be impacted depending on the level of sperm DNA damage.…”
Section: Discussionmentioning
confidence: 99%